Pengambilan Keputusan Pendanaan Ekuitas dan Pendanaan Hutang Pada Perusahaan Retail di Indonesia (Pengujian Teori Struktur Modal) (Business and Accounting Education Journal, 2022)
The purpose of this study was to analyze the influence of market and operating performance on corporate funding behavior. The object of research is the use of the financial statements of retail go-public companies on the Indonesia Stock Exchange in 2016 - 2020. The population to be studied in this study are retail companies that go-public on the Indonesia Stock Exchange for the period 2016 to 2020 with a total of 26 companies and using a sample aim. Data collected by documentation method. Data were analyzed by multiple linear regression with the smart pls application. The results of the study show (1) there is no influence between Profitability (ROA) and Leverage (D.TH), (2) there is no effect between Profitability (ROA) and Equity (D.MS), (3) there is no influence between Profitability ( ROA) with Double Funding (D.TH + D.MS), (4) there is no influence between Market Value (PBV) and Leverage (D.TH), (5) There is an influence between Market Value (PBV) and Equity (D .MS) (6) There is an influence between Market Value (PBV) and Double Funding (D.TH + D.MS).